The study and realization of BDS un-differenced network-RTK based on raw observations. Issue 11 (1st June 2017) - Tu, Rui; Zhang, Pengfei; Zhang, Rui; Lu, Cuixian; Liu, Jinhai; Lu, Xiaochun
Abstract: A BeiDou Navigation Satellite System (BDS) Un-Differenced (UD) Network Real Time Kinematic (URTK) positioning algorithm, which is based on raw observations, is developed in this study. Given an integer ambiguity datum, the UD integer ambiguity can be recovered from Double-Differenced (DD) integer ambiguities, thus the UD observation corrections can be calculated and interpolated for the rover station to achieve the fast positioning. As this URTK model uses raw observations instead of the ionospheric-free combinations, it is applicable for both dual- and single-frequency users to realize the URTK service. The algorithm was validated with the experimental BDS data collected at four regional stations from day of year 080 to 083 in 2016. The achieved results confirmed the high efficiency of the proposed URTK for providing the rover users a rapid and precise positioning service compared to the standard NRTK. In our test, the BDS URTK can provide a positioning service with cm level accuracy, i.e., 1 cm in the horizontal components, and 2–3 cm in the vertical component. Within the regional network, the mean convergence time for the users to fix the UD ambiguities is 2.7 s for the dual-frequency observations and of 6.3 s for the single-frequency observations after the DD ambiguity resolution. Furthermore, due to the feature of realizing URTK technology under the UD processing mode, it is possible to integrate the global Precise Point Positioning (PPP) and the local NRTK into a seamless positioning service.